Research on the force mechanism of the connection between the foundation ring and the anchor cage ring of the high-altitude onshore wind turbine. Issue 1 (1st January 2022) - Xu, Jianjun; Chen, Kang; Yang, Yunfeng; Zhang, Fenghua; Meng, Wenqiang; Zou, Wuting; Xi, Yu; Peng, Huaiwu
Abstract: The most widely used connection form of the wind turbine foundation and the tower is the foundation ring method. With the popularization and application of high wheel hub and large-capacity wind turbines, the anchor cage ring has gradually become the connection method of large-capacity wind turbines. Therefore, the force mechanism of the connection between the foundation ring and the anchor cage ring has become an important issue in the basic design of the wind turbine. In this paper, numerical simulation method is used to analyse the characteristics of the two connection methods and force characteristics of the foundation ring and anchor bolts. The force transmission mechanism and force characteristics of the two connection methods are summarized and the stress distribution of the foundation ring, the anchor cage ring and the nearby concrete are obtained. Finally, the basic strengthening strategies under the two connection methods are clarified.